The effect of palm oil fuel ash (POFA) with limestone as a partial cement replacement material toward concrete microstructure and hydration - Nur Ayna, Azmi (2015)
Malaysia as the world’s largest exporter of palm oil has been facing problem in disposing palm oil fuel ash (POFA), a by-product of palm oil mills since many years ago. POFA is one of waste material that can be used as pozzolanic or fillers or replacement for the cement in concrete. This research is important to compare the effectiveness using POFA as a partial cement replacement material towards concrete microstructure and concrete hydration. The quality of POFA was improved by grinding until the median particles sizes is about 63 μm. At the first stage, each series of concrete test is design for grade 30. Four types of mixes are prepared. One consists of a control mix whereas another three consists of 20% of POFA, 20% of POFA with 5% of limestone and 20% of POFA with 10% of limestone respectively. For the compressive strength, concrete cubes 150 x 150 x 150 mm was tested due to 7 days, 28 days and 90 days of curing ages. From the testing carried out, it was found that, the compressive strength of POFA concrete was much lower than that of concrete without POFA. Although the strength of POFA concrete did not exceed the characteristic strength, the compressive strength of POFA concrete is slightly increased at 90 days. An analytical methods used to investigate the microstructure of the POFA include X-ray Diffraction (XRD), Thermogravimetric analysis (TGA) and Scanning Electron Microscopy (SEM).Based on XRD analysis leads to the fact that the existence of C-S-H increased with curing age indicating the progress of cement hydration reaction and pozzolanic reaction. From the microstructural analysis (SEM) shows the existing of C-S-H gel has lead to a densification structure and increase the strength of concrete. Hexagonal platelets of Ca(OH)2 could be observed in some of samples. As a conclusion, it found that replacement of cement with 20% of POFA has achieved the pozzolanic reaction and also can improve the pore structure of the concrete.